Influence of Feeding Processed Pigeon Pea (Cajanus cajan) Seeds on Broiler Chick Performance - Abdelati, Khadiga Abbas; Mohammed, Hashim Abdel Rahman; Ahmed, Mohamed Elamin (International Journal of Poultry Science, 2009)
This experiment was conducted to assess the effect of feeding different processed pigeon pea seeds on broilers performance. Four isocaloric and iso-nitrogenous diets containing (10%) of soaked pigeon pea seeds, decorticated with added enzyme (multi enzymes with high content of pentosanase), decorticated roasted and control diet were formulated. Parameters measured weekly were feed intake, body weight gain and Feed Conversion Ratio (FCR). Overall body weight, hot carcass weight and dressing percentage were recorded. Results revealed that inclusion of 10% soaked pigeon pea seed, decorticated with added enzyme (multi enzyme with a high content of pentosanase) and decorticated roasted had no significant (p>0.05) effects on feed intake, weight gain, feed conversion ratio, final live body weight, hot carcass weight and dressing percentage. Inclusion of 10% processed pigeon pea seeds resulted in a similar performance of broiler chicks when compared with the control group.